Human Excreta Estimation for Biogas Production in the University of Abuja, Nigeria - Akerele, O. T.; Zarmai, M. T.; Ogwueleka, T.C.; Samson, B.; Ogbo, O. S.; Abdullahi, I. (Journal of Environment, 2025)
Purpose: Effective waste management is crucial for institutions like the University of Abuja, and estimating the availability of human excreta is essential in this regard. The purpose of this study is anchored in the critical need to develop sustainable energy solutions and waste minimization in the face of escalating global energy demands and environmental concerns. By estimating the availability of human excreta for biogas production, this study aims to contribute to the promotion of renewable energy, waste reduction, and environmental stewardship at both local and global scales. Methodology: This dissertation employs computational models, specifically the pseudo-inverse and predator-prey models, to derive an estimator for the availability of faecal matter. The pseudo-inverse component determines faecal matter availability linearly, while the predator-prey component accounts for depreciation due to storage. Additionally, the human excreta were characterized using both proximate and ultimate analysis. The proximate analysis considered pH, moisture content, volatile solid, total solids, total nitrogen, total organic carbon, carbon to nitrogen ratio (C/N) and chemical oxygen demand (COD). The ultimate analysis considered Fe, Zn, Mn, B, and Cu. Findings: The outcome of this study indicated the characterized human excreta from the University of Abuja main campus shows promising potential for biogas production; however, careful management and possibly some adjustments would be necessary to optimize the process. From survey data, the model estimates an average deposition of 25.42 m3 /day of faecal matter at a decay rate of -0.003938 per hour can generate 13.53 Mega-Joule of biogas per day. This showcases the potential and sustainability of biogas production from the university's hostels. Unique Contribution to Theory, Policy and Practice: The study concludes that human excreta is a viable resource for biogas production at the University of Abuja, highlighting the quantity generated and its feasibility for utilization. Recommendations include investing in infrastructure, continuing research and development efforts, and garnering policy support to leverage human excreta for sustainable biogas production.